Biological synopsis of Photocryptus Viereck (Hymenoptera, Ichneumonidae, Cryptinae), with eight new host records and fourteen new geographic records - Aguiar, Alexandre P.; Santos, Bernardo F. (Zootaxa, 2009)
The host records of Photocryptus Viereck are revised. Nine species from seven genera and four families, all aculeate Hymenoptera, are recognized as hosts for species of Photocryptus. Published host records were compiled for three species, and eight new records are provided for four species, as follows: P. concinnus (Brullé) is parasitoid of Auplopus militaris (Lynch-Arribalzaga) (Pompilidae, Pepsinae) new record, Sceliphron assimile (Dahlbom) (Sphecidae, Sceliphrinae), new record, and Trypoxylon maidli Richards (Crabronidae, Trypoxyloninae), new record; P. fumatus (Hancock) is parasitoid of Santamenes novarae (Saussure) (Vespidae, Eumeninae), and Sceliphron assimile, new record; P. pachymenae (Cresson) is parasitoid of Pachymenes sp. (Vespidae, Eumeninae), and Sceliphron fistularium (Dahlbom); P. photomorphus Viereck is parasitoid of Sceliphron sp. and Brachymenes dyscherus (Saussure) (Vespidae, Eumeninae); P. testaceoniger (Taschenberg) is parasitoid of Sceliphron fistularium, new record; P. testaceus (Taschenberg) is parasitoid of Sceliphon fistularium, new record, Trypoxylon albitarse Fabricius, new record, and T. nitidum F. Smith, new record. A non-identified species of Photocryptus is recorded in the literature parasiting Trigonopsis violascens Dalla Torre (Sphecidae, Sceliphrinae). Original data provides the first evidence of two species of Photocryptus attacking the same host nest, namely P. testaceoniger and P. testaceus on a nest of S. fistularium; ovipositor length vs. nest dimensions are also compared for these species, suggesting either incidental attack or avoidance of confrontation behavior. Fourteen new geographic records are provided for seven species.